A practical guide to group facilitation : the threefold approach - Korff, Yorck von (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"A Practical Guide to Group Facilitation introduces a unique threefold approach to facilitation, blending Person-Centered Practice, system knowledge, and method expertise together. It serves as a comprehensive resource for facilitators seeking to enhance their professional skills. The book delves into the significance of Person-Centered Practice as the cornerstone of facilitation, exploring personal facilitator qualities like congruence, empathic listening, and unconditional positive regard, inspired by the principles of Carl Rogers. It successfully integrates Jane Loevinger's personal development theories with facilitator skill development, illustrating the symbiotic relationship between personal growth and effective facilitation. Additionally, the book incorporates Nonviolent Communication (NVC) into the facilitator's toolkit, offering practical strategies for navigating challenging situations. It covers a spectrum of facilitation methods, from structured approaches to the Person-Centered style of Carl Rogers, equipping facilitators to face diverse group contexts. Presenting valuable skills and insights to enhance professional practice, this book will be highly relevant reading for facilitators, mediators and those offering training. It will also be useful reading for professionals in participatory processes such as coaches, team leaders, organisational leaders, managers and mentors"--
Keywords: Group facilitation; Social psychology; PSYCHOLOGY / Social Psychology